2016
DOI: 10.1111/jfd.12526
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of host‐seeking behaviour by the salmon louse, Lepeophtheirus salmonis, using botanically derived repellents

Abstract: The potential for developing botanically derived natural products as novel feed-through repellents for disrupting settlement of the salmon louse, Lepeophtheirus salmonis (Caligidae) upon farmed Atlantic salmon, Salmo salar, was investigated using an established laboratory vertical Y-tube behavioural bioassay for assessing copepodid behaviour. Responses to artificial sea water conditioned with the odour of salmon, or to the known salmon-derived kairomone component, α-isophorone, in admixture with selected botan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…2013; O’Shea et al . 2017). Indeed, some existing commercially available functional feeds are claimed to reduce attraction of lice towards fish (e.g.…”
Section: What Preventative Methods Are Available?mentioning
confidence: 99%
“…2013; O’Shea et al . 2017). Indeed, some existing commercially available functional feeds are claimed to reduce attraction of lice towards fish (e.g.…”
Section: What Preventative Methods Are Available?mentioning
confidence: 99%
“…Some existing commercial feeds are claimed to contain repellent semiochemical additives and European patents exist for some methods and feed compositions for masking fish semiochemicals (e.g., European Patent Number EP2517568A1). Research has shown that ectoparasite infections on fish (amberjack, Nile tilapia and rainbow trout) are reduced when the fish are grown using diets containing plant derived extracts or beta‐glucan additives 600–603 and proof‐of‐concept evidence has shown that botanically‐derived materials can be incorporated into feed additives to reduce the attraction of L. salmonis to salmonid host cues 604 . Increased knowledge about genetic differences in semiochemical production between resistant and susceptible hosts to sea lice infection may help in the design of the formulation of feed additives for use to boost Atlantic salmon's ability to resist sea lice infection.…”
Section: Technologies and Approaches For Boosting Host Resistancementioning
confidence: 99%
“…These seek the upper layers of water when attaching to the host, an observation that was exploited by Geitung et al (2019) when constructing snorkel cages to prevent copepodids from attacking salmon kept at lower water depths. Still other ideas were developed that included the use of herbal repellents to jam the parasite's host finding (O'Shea et al , 2016). Genetic markers for susceptibility have been identified (Gharbi et al , 2009), and quantitative trait loci for resistance in salmon have been described (Robledo et al , 2019), which may lead to development of breeding programmes to obtain salmon with a higher natural resistance to infection.…”
Section: Parasites In Aquaculturementioning
confidence: 99%